Super-amphiphilic coating capable of conducting lithium ions, preparation method and application of super-amphiphilic coating, diaphragm, pole piece and lithium ion battery

By applying a super-parent coating that can conduct lithium ions on the separator and pole surface of the lithium-ion battery, the problems of uneven reflux of the electrolyte and lithium-ion evolution are solved, and the cycle life of the battery cell is improved.

CN119231096AActive Publication Date: 2024-12-31JIANGSU PYLON BATTERY CO LTD

Patent Information

Application Number
CN202411353515.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

During the charging and discharging of lithium-ion batteries, the electrode material expands and contracts, resulting in uneven return of the electrolyte, resulting in local liquid lean and lithium excretion, affecting the cycle life of the battery cell.

Method used

Using a super-parent coating that can conduct lithium ions, the surface of the lithium-ion conductor nanomaterial is coated to form a micro-nano structure, which improves the suction and liquid retention ability of the electrolyte, and is used for the separator and pole sheet surface of the battery. .

Benefits of technology

Effectively alleviate the extrusion of the electrolyte during the expansion process, improve the liquid absorption capacity of the battery cell, reduce lithium extraction during the circulation process, and extend the cycle life of the battery cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119231096A_ABST
    Figure CN119231096A_ABST
Patent Text Reader

Abstract

The invention provides a super-amphiphilic coating capable of conducting lithium ions, a preparation method and application of the super-amphiphilic coating, a diaphragm, a pole piece and a lithium ion battery, and relates to the technical field of batteries. The invention provides a super-amphiphilic coating capable of conducting lithium ions. The super-amphiphilic coating comprises an amphiphilic material and a lithium ion conductor nano material, the surface of the lithium ion conductor nanometer material is coated with the amphiphilic material. Wherein the lithium ion conductor nanometer material provides good lithium ion conduction performance, the amphiphilic material coating layer and the lithium ion conductor nanometer material form a micro-nano structure, and super-oleophylic and super-hydrophilic capabilities can be provided. Therefore, the super-amphiphilic coating provided by the invention can be used as a coating of a diaphragm and a current collector of a lithium ion battery, and the super-amphiphilic coating has extremely high electrolyte affinity, so that the back absorption of an electrolyte can be accelerated, the liquid absorption capacity of a battery cell is improved, and meanwhile, the exertion of electrochemical performance is not influenced; and the micro-nano structure and the polymer component of the super-amphiphilic coating have relatively good liquid retention capability, so that the extrusion of electrolyte in the expansion process can be relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a super-amphiphilic coating capable of conducting lithium ions, a preparation method and application thereof, a diaphragm, a pole piece and a lithium ion battery. Background Art

[0002] With the development of technology, lithium-ion batteries have been widely used in many fields such as consumer electronics, power, energy storage, etc. Due to higher requirements for application scenarios and increasingly fierce market competition, lithium-ion batteries with high energy density, high power density, high safety and long life have become the development focus of major battery manufacturers.

[0003] However, during the charge and discharge process of lithium-ion batteries, the electrode materials continue to expand and contract, and the electrolyte between the battery cell pole pieces and the pole piece layers is squeezed out, and flows back into the restored pores after the volume of the electrode material shrinks. In this process, uneven electrolyte reflux and local electrolyte deficiency may occur, and lithium precipitation occurs at the electrolyte deficiency location due to insufficient lithium ion conductivity, causing unpredictable cycle "diving" of the battery cell, seriously affecting the cycle life of the battery cell.

[0004] Literature research suggests that the electrolyte first wets the separator and then diffuses into the electrode; if the electrode is not fully wetted, a non-wetting phase will be found near the electrode / current collector interface, and the membrane side is relatively fully wetted. Based on this, it is crucial to improve the ability of the pole piece and separator to reabsorb the electrolyte, and improving the wettability of the pole piece and separator with the electrolyte is the key to improving the absorption capacity. Currently, the commonly used solvents in commercial lithium-ion battery electrolytes include ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC), and commercial electrolytes are a mixture of multiple solvents. Therefore, it is necessary to develop a solution suitable for improving the wettability of multiple electrolytes.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The first object of the present invention is to provide a super amphiphilic coating that can conduct lithium ions to solve the above technical problems.

[0007] The second object of the present invention is to provide a method for preparing the above-mentioned super-amphiphilic coating capable of conducting lithium ions.

[0008] The third object of the present invention is to provide an application of the above-mentioned super-amphiphilic coating capable of conducting lithium ions in a battery.

[0009] A fourth object of the present invention is to provide a diaphragm.

[0010] A fifth object of the present invention is to provide a pole piece.

[0011] A sixth object of the present invention is to provide a lithium ion battery.

[0012] In order to achieve the above objectives, the following technical solutions are adopted:

[0013] In a first aspect, the present invention provides a super-amphiphilic coating capable of conducting lithium ions, comprising an amphiphilic material and a lithium ion conductor nanomaterial; the amphiphilic material is coated on the surface of the lithium ion conductor nanomaterial;

[0014] The amphiphilic material comprises at least one of propoxyglycerol triglycidyl ether polymer, polyvinyl pyrrolidone, polydopamine, polyethylene glycol-polytetramethyl ether glycol copolymer or polyethylene glycol-polydimethylsiloxane copolymer;

[0015] The lithium ion conductor nanomaterial includes at least one of a NASICON type oxide solid electrolyte, a LISICON type oxide solid electrolyte, a Garnet type oxide solid electrolyte, a Perovskite type oxide solid electrolyte or an Antiperovskit type oxide solid electrolyte;

[0016] The particle size of the lithium ion conductor nanomaterial is 10200 nm.

[0017] As a further technical solution, the mass ratio of the amphiphilic material to the lithium ion conductor nanomaterial is 0.01:110:1.

[0018] As a further technical solution, the static contact angle of the super-amphiphilic coating with water-based solvents is less than 5°, and the static contact angle of the super-amphiphilic coating with oil-based solvents is less than 5°.

[0019] As a further technical solution, the NASICON type oxide solid electrolyte comprises Li 1.4 Al 0.4 Ti 1.6 (PO4)3 or Li 1.5 Al 0.5 Ge 1.5 (PO4)3;

[0020] The LISICON-type oxide electrolyte includes γLi3PO4;

[0021] The Garnet-type oxide solid electrolyte includes Li7La3Zr2O 12 or Li5La3Ta2O 12 ;

[0022] The Perovskite-type oxide solid electrolyte includes Li 0.5 La 0.5 TiO3;

[0023] The Antiperovskite-type oxide solid electrolyte includes Li3OCl.

[0024] In a second aspect, the present invention provides a method for preparing the above-mentioned super-amphiphilic coating capable of conducting lithium ions, comprising the following steps:

[0025] The amphiphilic material or its precursor, a lithium ion conductor nanomaterial and a solvent are mixed to form a dispersion, and then the dispersion is applied and dried to prepare the super amphiphilic coating capable of conducting lithium ions;

[0026] The solvent includes at least one of ethanol, deionized water, n-hexane, tetrahydrofuran (THF), heptane, isopropanol, carbon trichloride or carbon tetrachloride.

[0027] As a further technical solution, in the dispersion, the mass proportion of the lithium ion conductor nanomaterial is 0.1%-10%.

[0028] In a third aspect, the present invention provides the use of the above-mentioned super-amphiphilic coating capable of conducting lithium ions in a battery.

[0029] In a fourth aspect, the present invention provides a separator, comprising a base film, the surface of the base film being coated with the super-amphiphilic coating capable of conducting lithium ions.

[0030] In a fifth aspect, the present invention provides a pole piece, comprising a current collector, the surface of the current collector being coated with the super-amphiphilic coating capable of conducting lithium ions.

[0031] In a sixth aspect, the present invention provides a lithium-ion battery, comprising the above-mentioned diaphragm and / or the above-mentioned pole piece.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The present invention provides a super-amphiphilic coating that can conduct lithium ions, wherein the lithium ion conductor nanomaterial provides good lithium ion conduction performance, and the amphiphilic coating layer and the lithium ion conductor nanomaterial constitute a micro-nano structure, which can provide super-oleophilic and super-hydrophilic capabilities. Therefore, the super-amphiphilic coating that can conduct lithium ions provided by the present invention can be used as a coating for the separator and current collector of a lithium ion battery, and its extremely strong affinity for electrolyte can accelerate the reabsorption of the electrolyte and improve the liquid absorption capacity of the battery core without affecting the electrochemical performance; and the micro-nano structure and polymer component of the super-amphiphilic coating have good liquid retention capacity, which helps to alleviate the extrusion of the electrolyte during the expansion process; in general, the super-amphiphilic coating that can conduct lithium ions provided by the present invention can effectively alleviate the lithium precipitation caused by the lack of liquid in the middle of the battery core during the cycle process, and improve the cycle life of the battery core. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0035] Figure 1 Schematic diagram of the structure of the superamphiphilic coating that can conduct lithium ions.

[0036] Icons: 1-Lithium ion conductor nanomaterials; 2-amphiphilic materials; 10-superamphiphilic coatings that can conduct lithium ions. DETAILED DESCRIPTION

[0037] The embodiments of the present invention will be described in detail below in conjunction with the embodiments and examples, but it will be appreciated by those skilled in the art that the following embodiments and examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified, proceed according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0038] In the first aspect, the present invention provides a super-amphiphilic coating 10 capable of conducting lithium ions, comprising an amphiphilic material 2 and a lithium ion conductor nanomaterial 1; the amphiphilic material 2 is coated on the surface of the lithium ion conductor nanomaterial 1, and the structural schematic diagram of the coating is as shown in Figure 1 As shown;

[0039] The amphiphilic material 2 includes but is not limited to at least one of propoxyglycerol triglycidyl ether polymer, polyvinyl pyrrolidone, polydopamine, polyethylene glycol-polytetramethyl ether glycol copolymer or polyethylene glycol-polydimethylsiloxane copolymer, or other materials with amphiphilic effects known to those skilled in the art;

[0040] The lithium ion conductor nanomaterial 1 includes but is not limited to at least one of a NASICON type oxide solid electrolyte, a LISICON type oxide solid electrolyte, a Garnet type oxide solid electrolyte, a Perovskite type oxide solid electrolyte or an Antiperovskit type oxide solid electrolyte;

[0041] The particle size of the lithium ion conductor nanomaterial 1 is 10200 nm.

[0042] The super-amphiphilic coating that can conduct lithium ions provided by the present invention, wherein the lithium ion conductor nanomaterial provides good lithium ion conduction performance, and the amphiphilic material coating layer and the lithium ion conductor nanomaterial constitute a micro-nano structure, which can provide super-oleophilic and super-hydrophilic capabilities. Therefore, the super-amphiphilic coating that can conduct lithium ions provided by the present invention can be used as a coating for the separator and current collector of a lithium ion battery, and its extremely strong affinity for electrolyte can accelerate the reabsorption of the electrolyte and improve the liquid absorption capacity of the battery core without affecting the electrochemical performance; and the micro-nano structure and polymer component of the super-amphiphilic coating have good liquid retention capacity, which helps to alleviate the extrusion of the electrolyte during the expansion process.

[0043] In some optional embodiments, the mass ratio of the amphiphilic material to the lithium ion conductor nanomaterial may be, for example, but not limited to, 0.01:1, 0.1:1, 1:1 or 10:1.

[0044] In some optional embodiments, the thickness of the super-amphiphilic coating capable of conducting lithium ions is 100 nm to 10 μm, for example, but not limited to 100 nm, 1 μm or 10 μm.

[0045] In some optional embodiments, the super-amphiphilic coating has a static contact angle of less than 5° for aqueous solvents, a static contact angle of less than 5° for oil-based solvents, and a static contact angle of less than 5° for various electrolytes.

[0046] In some optional embodiments, the NASICON type oxide solid electrolyte includes but is not limited to Li 1.4 Al 0.4 Ti 1.6 (PO4)3 or Li 1.5 Al 0.5 Ge 1.5 (PO4)3;

[0047] The LISICON type oxide electrolyte is not limited to γLi3PO4;

[0048] The Garnet-type oxide solid electrolyte includes but is not limited to Li7La3Zr2O 12 or Li5La3Ta2O 12 ;

[0049] The Perovskite-type oxide solid electrolyte includes but is not limited to Li 0.5 La 0.5 TiO3;

[0050] The Antiperovskite-type oxide solid electrolyte includes but is not limited to Li3OCl.

[0051] In a second aspect, the present invention provides a method for preparing the above-mentioned super-amphiphilic coating capable of conducting lithium ions, comprising the following steps:

[0052] The amphiphilic material or its precursor, a lithium ion conductor nanomaterial and a solvent are mixed to form a dispersion, and then the dispersion is applied and dried to prepare the super amphiphilic coating capable of conducting lithium ions;

[0053] The solvent includes at least one of ethanol, deionized water, n-hexane, tetrahydrofuran (THF), heptane, isopropanol, carbon trichloride or carbon tetrachloride.

[0054] The preparation method is simple and convenient, and the prepared super-amphiphilic coating capable of conducting lithium ions has good super-oleophilic and super-hydrophilic capabilities.

[0055] In some optional embodiments, in the dispersion, the mass proportion of the lithium ion conductor nanomaterial may be, for example, but not limited to, 0.1%, 1% or 10%.

[0056] In some optional embodiments, the mixing method includes one or more of magnetic stirring, vortex oscillation, ultrasonic oscillation or mechanical stirring;

[0057] The mixing temperature is room temperature, and the mixing time is 1 hour to 48 hours.

[0058] In some optional embodiments, the coating method includes any one of spraying, spin coating, dipping, blade coating, and brush coating.

[0059] In some optional embodiments, the drying method includes: volatilization at room temperature for 4 to 24 hours; or, heat treatment in an oven at 40-120° C. for 4 to 24 hours.

[0060] In a third aspect, the present invention provides the use of the above-mentioned super-amphiphilic coating capable of conducting lithium ions in a battery.

[0061] The super-amphiphilic coating capable of conducting lithium ions provided by the present invention is applied to a battery, which can effectively improve the battery's liquid retention capacity.

[0062] In a fourth aspect, the present invention provides a separator, comprising a base film, the surface of the base film being coated with the super-amphiphilic coating capable of conducting lithium ions.

[0063] In a fifth aspect, the present invention provides a pole piece, comprising a current collector, the surface of the current collector being coated with the super-amphiphilic coating capable of conducting lithium ions.

[0064] In a sixth aspect, the present invention provides a lithium-ion battery, comprising the above-mentioned diaphragm and / or the above-mentioned pole piece.

[0065] The super-amphiphilic coating capable of conducting lithium ions provided by the present invention is used as a coating for the separator and current collector of a lithium-ion battery. Its extremely strong affinity for electrolyte can accelerate the reabsorption of the electrolyte and improve the liquid absorption capacity of the battery core without affecting the electrochemical performance. Moreover, the micro-nano structure and polymer components of the super-amphiphilic coating have good liquid retention capacity, which helps to alleviate the extrusion of the electrolyte during the expansion process.

[0066] The present invention is further described below by means of specific examples and comparative examples. However, it should be understood that these examples are only used for more detailed description and should not be construed as limiting the present invention in any form.

[0067] Example 1

[0068] In this embodiment, an oxide solid electrolyte Li1.4Al0.4Ti1.6(PO4)3 with a particle size of 50-100nm is selected as a lithium ion conductive particle, and a propoxyglycerol triglycidyl ether (GPTE)-based amphiphilic polymer is constructed on its surface as a coating layer through coupling reaction and cross-linking reaction, and then a super amphiphilic coating capable of conducting lithium ions is prepared on the surface of aluminum foil. The specific steps are as follows:

[0069] 1. Add Li1.4Al0.4Ti1.6(PO4)3 particles with a particle size of 50-100 nm into a mixed liquid of anhydrous ethanol and 1-methylpyrrole (V:V=100:0.01), and stir rapidly at room temperature to fully disperse;

[0070] 2. Add the precursors of the amphiphilic material, propoxyglycerol triglycidyl ether (GPTE) and octadecylamine (ODA) (the mass ratio of the two is 50:1) to the dispersion, and prepare the dispersion with the precursor and Li1.4Al0.4Ti1.6(PO4)3 particles in a mass ratio of 1:10. Stir at room temperature for 6 hours and at 50°C for 15 minutes to obtain a uniform dispersion. The mass proportion of Li1.4Al0.4Ti1.6(PO4)3 particles in the dispersion is about 0.1%;

[0071] 3. Spray the above dispersion evenly on the aluminum foil;

[0072] 4. Dry the aluminum foil at room temperature for 5 minutes, and heat at 150° C. for 1 hour to complete crosslinking and curing, thereby obtaining an aluminum foil having a super-amphiphilic coating that can conduct lithium ions and is constructed by Li1.4Al0.4Ti1.6(PO4)3 nanoparticles coated with an amphiphilic polymer, wherein the thickness of the coating is 2 μm;

[0073] 5. Preparation of a lithium-ion battery comprising the above-mentioned positive electrode sheet:

[0074] (1) Preparing a positive electrode sheet having an aluminum foil surface coated with the super-amphiphilic coating capable of conducting lithium ions:

[0075] The positive electrode active material LiFePO4, conductive carbon black (Super P) and binder polytetravinylidene fluoride (PVDF) are uniformly mixed in a proper amount of N-methylpyrrolidone (NMP) at a mass ratio of 97.3:1.2:1.5 to prepare a positive electrode slurry, and the positive electrode slurry is coated on the above-mentioned aluminum foil with the super amphiphilic coating that can conduct lithium ions, and the positive electrode sheet is prepared through rolling, slitting, punching and other processes;

[0076] (2) Preparation of negative electrode sheet:

[0077] The negative electrode active material artificial graphite, the conductive agent carbon black (Super P), the binder styrene butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC Na) are mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 95.5:1.7:1.6:1.2 to obtain a negative electrode slurry, the negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through rolling, slitting, punching and other processes;

[0078] (3) Preparation of diaphragm:

[0079] Use commercial polypropylene diaphragms;

[0080] (4) Preparation of electrolyte:

[0081] A mixed solvent was prepared by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) at a mass ratio of 50:50, and then fully dried electrolyte salt LiPF6 was dissolved therein (1.0 mol / L) to obtain an electrolyte solution.

[0082] (5) Preparation of lithium-ion batteries

[0083] The positive electrode sheet, the separator and the negative electrode sheet are stacked in order to obtain the electrode core; the electrode core is placed in an outer package and baked; the electrolyte is injected into the dried lithium-ion battery, and a secondary battery is prepared through the processes of standing, forming, vacuum packaging, aging, and capacity division.

[0084] Example 2

[0085] In this embodiment, an oxide solid electrolyte Li1.5Al0.5Ge1.5(PO4)3 with a particle size of 50-100nm is selected as a lithium ion conductive particle, and a polyvinyl pyrrolidone (PVP) amphiphilic polymer coating layer is constructed on its surface by a liquid phase coating method, and then a super amphiphilic coating capable of conducting lithium ions is prepared on the surface of a polypropylene diaphragm. The specific steps are as follows:

[0086] 1. Add Li1.5Al0.5Ge1.5(PO4)3 particles with a particle size of 50-100nm into a PVP aqueous solution, with a mass ratio of PVP to Li1.5Al0.5Ge1.5(PO4)3 of 1:5, disperse with ultrasound assistance at room temperature, and react for 6 hours under mechanical stirring to obtain a uniform dispersion, in which the mass proportion of Li1.5Al0.5Ge1.5(PO4)3 in the dispersion is 1%;

[0087] 2. Prepare the coating on both sides of the polypropylene diaphragm by dipping, immerse the diaphragm in the above dispersion for 5 seconds and then take it out;

[0088] 3. The above-mentioned diaphragm was placed at room temperature for 12 hours to evaporate the water, and was placed in a vacuum oven at 60° C. for 24 hours to further remove the solvent, thereby obtaining a diaphragm having a super-amphiphilic coating that can conduct lithium ions and is constructed of Li1.5Al0.5Ge1.5(PO4)3 nanoparticles coated with polyvinyl pyrrolidone, and the thickness of the coating is 5 μm;

[0089] 4. Preparation of a lithium-ion battery comprising the above-mentioned separator:

[0090] (1) Preparation of positive electrode sheet:

[0091] The positive electrode active material LiFePO4, conductive carbon black (Super P) and binder polytetravinylidene fluoride (PVDF) are uniformly mixed in a proper amount of N-methylpyrrolidone (NMP) at a mass ratio of 97.3:1.2:1.5 to prepare a positive electrode slurry, the positive electrode slurry is coated on a current collector aluminum foil, and the positive electrode sheet is prepared through processes such as rolling, slitting and punching.

[0092] (2) Preparation of negative electrode sheet:

[0093] The negative electrode active material artificial graphite, the conductive agent carbon black (Super P), the binder styrene butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC Na) are mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 95.5:1.7:1.6:1.2 to obtain a negative electrode slurry, the negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through rolling, slitting, punching and other processes;

[0094] (3) Diaphragm:

[0095] The isolation membrane adopts the membrane with a super-amphiphilic coating that can conduct lithium ions, which is constructed in the embodiment of the present application;

[0096] (4) Preparation of electrolyte:

[0097] A mixed solvent was prepared by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) at a mass ratio of 50:50, and then fully dried electrolyte salt LiPF6 was dissolved therein (1.0 mol / L) to obtain an electrolyte solution.

[0098] (5) Preparation of lithium-ion batteries

[0099] The positive electrode sheet, the separator and the negative electrode sheet are stacked in order to obtain the electrode core; the electrode core is placed in an outer package and baked; the electrolyte is injected into the dried lithium-ion battery, and a secondary battery is prepared through the processes of standing, forming, vacuum packaging, aging, and capacity division.

[0100] Example 3

[0101] In this embodiment, an oxide solid electrolyte Li7La3Zr2O12 with a particle size of 50-100 nm is selected as a lithium ion conductive particle, and a polyethylene glycol (PEG)-polydimethylsiloxane (PDMS) copolymer is constructed on its surface by in-situ polymerization as a coating layer, and then a super-amphiphilic coating capable of conducting lithium ions is prepared on the surface of the copper foil. The specific steps are as follows:

[0102] 1. PEG (Mn = 2000) and PDMS (Mn = 1810) were added in a molar ratio of 1:1 and dissolved in tetrahydrofuran solvent (10 wt / vol%);

[0103] 2. Add Li7La3Zr2O12 particles with a particle size of 50-100 nm, hexamethylene diisocyanate and dibutyltin dilaurate to the above solution, and the mass ratio of polymer precursors PEG and PDMS to Li7La3Zr2O12 is 1:1. Stir at room temperature for 24 hours, and finally obtain a uniform dispersion as the coupling reaction proceeds;

[0104] 3. The prepared dispersion was precipitated, washed with deionized water for 3 times, and then vacuum dried at 80°C for 24 hours to obtain Li7La3Zr2O12 nanoparticles coated with PEG-PDMS copolymer;

[0105] 4. Dispersing the Li7La3Zr2O12 nanoparticles coated with the PEG-PDMS copolymer in deionized water, preparing a dispersion by magnetic stirring at room temperature and subsequent ultrasonic dispersion, wherein the mass proportion of Li7La3Zr2O12 in the dispersion is about 5%;

[0106] 5. Use a doctor blade method to evenly apply the above dispersion on the copper foil;

[0107] 6. The above-mentioned diaphragm was placed at room temperature for 12 hours to evaporate the water, and was placed in a vacuum oven at 60° C. for 24 hours to further remove the solvent, thereby obtaining a copper foil having a super-amphiphilic coating that can conduct lithium ions and is constructed by Li7La3Zr2O12 nanoparticles coated with PEG-PDMS copolymer, and the thickness of the coating is 100 nm;

[0108] 7. Preparation of a lithium-ion battery comprising the above-mentioned negative electrode sheet:

[0109] (1) Preparation of positive electrode sheet:

[0110] The positive electrode active material LiFePO4, conductive carbon black (Super P) and binder polytetravinylidene fluoride (PVDF) are uniformly mixed in a proper amount of N-methylpyrrolidone (NMP) at a mass ratio of 97.3:1.2:1.5 to prepare a positive electrode slurry, and the positive electrode slurry is coated on the above-mentioned aluminum foil with the super amphiphilic coating that can conduct lithium ions, and the positive electrode sheet is prepared through rolling, slitting, punching and other processes;

[0111] (2) Preparing a negative electrode sheet having a copper foil surface coated with the super-amphiphilic coating capable of conducting lithium ions:

[0112] The negative electrode active material artificial graphite, the conductive agent carbon black (Super P), the binder styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC Na) are mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 95.5:1.7:1.6:1.2 to obtain a negative electrode slurry, and the negative electrode slurry is coated on the copper foil having the super-amphiphilic coating that can conduct lithium ions, and a negative electrode sheet is obtained through processes such as rolling, slitting, and punching.

[0113] (3) Preparation of diaphragm:

[0114] Use commercial polypropylene diaphragms;

[0115] (4) Preparation of electrolyte:

[0116] A mixed solvent was prepared by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) at a mass ratio of 50:50, and then fully dried electrolyte salt LiPF6 was dissolved therein (1.0 mol / L) to obtain an electrolyte solution.

[0117] (5) Preparation of lithium-ion batteries

[0118] The positive electrode sheet, the separator and the negative electrode sheet are stacked in order to obtain the electrode core; the electrode core is placed in an outer package and baked; the electrolyte is injected into the dried lithium-ion battery, and a secondary battery is prepared through the processes of standing, forming, vacuum packaging, aging, and capacity division.

[0119] Example 4

[0120] In this embodiment, an oxide solid electrolyte Li0.5La0.5TiO3 with a particle size of 10 50nm is selected as a lithium ion conductive particle, a polydopamine coating layer is constructed on its surface by in-situ polymerization, and then a super amphiphilic coating capable of conducting lithium ions is prepared on the surface of the diaphragm. The specific steps are as follows:

[0121] 1. Disperse Li0.5La0.5TiO3 nanoparticles in tris(hydroxymethyl)aminomethane hydrochloride buffer solution (50.0mmol / L, pH 8.5) at a dispersion ratio of about 1g / 1000ml;

[0122] 2. Add a certain amount of dopamine to the above dispersion, the mass ratio of dopamine to Li0.5La0.5TiO3 is about 10:1, and after stirring at room temperature for 12 hours, a uniform dispersion of polydopamine-coated Li0.5La0.5TiO3 is synthesized, and the mass proportion of Li0.5La0.5TiO3 in the dispersion is about 0.1%;

[0123] 3. Prepare the coating on both sides of the polypropylene diaphragm by dipping, immerse the diaphragm in the above dispersion for 5 seconds and then take it out;

[0124] 4. The above-mentioned diaphragm was placed at room temperature for 12 hours to evaporate the water, and was placed in a vacuum oven at 60° C. for 24 hours to further remove the solvent, thereby obtaining a diaphragm having a super-amphiphilic coating that can conduct lithium ions and is constructed of Li0.5La0.5TiO3 nanoparticles coated with polydopamine, and the thickness of the coating is 1 μm;

[0125] 5. Preparation of a lithium-ion battery comprising the above-mentioned separator:

[0126] (1) Preparation of positive electrode sheet:

[0127] The positive electrode active material LiFePO4, conductive carbon black (Super P) and binder polytetravinylidene fluoride (PVDF) are uniformly mixed in a proper amount of N-methylpyrrolidone (NMP) at a mass ratio of 97.3:1.2:1.5 to prepare a positive electrode slurry, the positive electrode slurry is coated on a current collector aluminum foil, and the positive electrode sheet is prepared through processes such as rolling, slitting and punching.

[0128] (2) Preparation of negative electrode sheet:

[0129] The negative electrode active material artificial graphite, the conductive agent carbon black (Super P), the binder styrene butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMCNa) are mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 95.5:1.7:1.6:1.2 to obtain a negative electrode slurry, and the negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through processes such as rolling, slitting, and punching.

[0130] (3) Diaphragm:

[0131] The isolation membrane adopts the membrane with a super-amphiphilic coating that can conduct lithium ions, which is constructed in the embodiment of the present application;

[0132] (4) Preparation of electrolyte:

[0133] A mixed solvent was prepared by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) at a mass ratio of 50:50, and then fully dried electrolyte salt LiPF6 was dissolved therein (1.0 mol / L) to obtain an electrolyte solution.

[0134] (5) Preparation of lithium-ion batteries

[0135] The positive electrode sheet, the separator and the negative electrode sheet are stacked in order to obtain the electrode core; the electrode core is placed in an outer package and baked; the electrolyte is injected into the dried lithium-ion battery, and a secondary battery is prepared through the processes of standing, forming, vacuum packaging, aging, and capacity division.

[0136] Example 5

[0137] In this embodiment, solid electrolyte Li3OCl with a particle size of 100200nm is selected as lithium ion conductive particles, polyethylene glycol (PEG)-polytetramethyl ether glycol (PTMEG) copolymer is constructed on its surface by in-situ polymerization as a coating layer, and then a super amphiphilic coating capable of conducting lithium ions is prepared on the surface of copper foil. The specific steps are as follows:

[0138] 1. PEG (Mn = 2000) and PTMEG (Mn = 2000) were added in a molar ratio of 1:1 and dissolved in tetrahydrofuran solvent (10 wt / vol%);

[0139] 2. Add Li3OCl particles with a particle size of 100-200 nm, hexamethylene diisocyanate and dibutyltin dilaurate to the above solution, and the mass ratio of the total mass of polymer precursors PEG and PTMEG to Li3OCl is 0.01:1. Stir at room temperature for 24 hours, and finally obtain a uniform dispersion as the coupling reaction proceeds;

[0140] 3. The prepared dispersion was precipitated, washed with deionized water three times, and then vacuum dried at 80° C. for 24 hours to obtain Li3OCl nanoparticles coated with PEG-PTMEG copolymer;

[0141] 4. Dispersing the Li3OCl nanoparticles coated with PEG-PTMEG copolymer in deionized water, preparing a dispersion by magnetic stirring at room temperature and subsequent ultrasonic dispersion, wherein the mass proportion of Li3OCl in the dispersion is about 10%;

[0142] 5. Use a doctor blade method to evenly apply the above dispersion on the aluminum foil;

[0143] 6. The above-mentioned separator was placed at room temperature for 12 hours to evaporate the water, and was placed in a vacuum oven at 60° C. for 24 hours to further remove the solvent, thereby obtaining an aluminum foil having a super-amphiphilic coating that can conduct lithium ions and is constructed by Li3OCl nanoparticles coated with PEG-PTMEG copolymer, and the thickness of the coating is 10 μm;

[0144] 7. Preparation of a lithium-ion battery comprising the above-mentioned positive electrode sheet:

[0145] (1) Preparing a positive electrode sheet having an aluminum foil surface coated with the super-amphiphilic coating capable of conducting lithium ions:

[0146] The positive electrode active material LiFePO4, conductive carbon black (Super P) and binder polytetravinylidene fluoride (PVDF) are uniformly mixed in a proper amount of N-methylpyrrolidone (NMP) at a mass ratio of 97.3:1.2:1.5 to prepare a positive electrode slurry, and the positive electrode slurry is coated on the above-mentioned aluminum foil with the super amphiphilic coating that can conduct lithium ions, and the positive electrode sheet is prepared through rolling, slitting, punching and other processes;

[0147] (2) Preparation of negative electrode sheet:

[0148] The negative electrode active material artificial graphite, the conductive agent carbon black (Super P), the binder styrene butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMCNa) are mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 95.5:1.7:1.6:1.2 to obtain a negative electrode slurry, and the negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through processes such as rolling, slitting, and punching.

[0149] (3) Preparation of diaphragm:

[0150] Use commercial polypropylene diaphragms;

[0151] (4) Preparation of electrolyte:

[0152] A mixed solvent was prepared by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) at a mass ratio of 50:50, and then fully dried electrolyte salt LiPF6 was dissolved therein (1.0 mol / L) to obtain an electrolyte solution.

[0153] (5) Preparation of lithium-ion batteries

[0154] The positive electrode sheet, the separator and the negative electrode sheet are stacked in order to obtain the electrode core; the electrode core is placed in an outer package and baked; the electrolyte is injected into the dried lithium-ion battery, and a secondary battery is prepared through the processes of standing, forming, vacuum packaging, aging, and capacity division.

[0155] Comparative Example 1

[0156] A coating, which is different from Example 1 in that the particle size of the lithium ion conductive particles is 1-5 μm.

[0157] In this embodiment, an oxide solid electrolyte Li1.4Al0.4Ti1.6(PO4)3 with a particle size of 1-5 μm is selected as a lithium ion conductive particle, and an amphiphilic polymer mainly composed of propoxyglycerol triglycidyl ether (GPTE) is constructed on its surface as a coating layer through coupling reaction and cross-linking reaction, and then a super amphiphilic coating capable of conducting lithium ions is prepared on the surface of aluminum foil. The specific steps are as follows:

[0158] 1. Add Li1.4Al0.4Ti1.6(PO4)3 particles with a particle size of 1-5 μm into a mixed liquid of anhydrous ethanol and 1-methylpyrrole (V:V=100:0.01), stir rapidly at room temperature to fully disperse, and the solid content of the dispersion is 0.1%;

[0159] 2. Add the precursors of the amphiphilic material, propoxyglycerol triglycidyl ether (GPTE) and octadecylamine (ODA) (the mass ratio of the two is 50:1) to the dispersion, and prepare the dispersion with the precursor and Li1.4Al0.4Ti1.6(PO4)3 particles in a mass ratio of 1:10. Stir at room temperature for 6 hours and at 50°C for 15 minutes to obtain a uniform dispersion. The mass proportion of Li1.4Al0.4Ti1.6(PO4)3 particles in the dispersion is about 0.1%;

[0160] 3. Spray the above dispersion evenly on the aluminum foil;

[0161] 4. Dry the aluminum foil at room temperature for 5 minutes, and heat at 150° C. for 1 hour to complete crosslinking and curing, thereby obtaining an aluminum foil having a super-amphiphilic coating that can conduct lithium ions and is constructed of Li1.4Al0.4Ti1.6(PO4)3 particles coated with an amphiphilic polymer, wherein the thickness of the coating is 2 μm;

[0162] 5. Preparation of a lithium-ion battery comprising the above-mentioned positive electrode sheet:

[0163] (1) Preparing a positive electrode sheet having an aluminum foil surface coated with the super-amphiphilic coating capable of conducting lithium ions:

[0164] The positive electrode active material LiFePO4, conductive carbon black (Super P) and binder polytetravinylidene fluoride (PVDF) are uniformly mixed in a proper amount of N-methylpyrrolidone (NMP) at a mass ratio of 97.3:1.2:1.5 to prepare a positive electrode slurry, and the positive electrode slurry is coated on the above-mentioned aluminum foil with the super amphiphilic coating that can conduct lithium ions, and the positive electrode sheet is prepared through rolling, slitting, punching and other processes;

[0165] (2) Preparation of negative electrode sheet:

[0166] The negative electrode active material artificial graphite, the conductive agent carbon black (Super P), the binder styrene butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMCNa) are mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 95.5:1.7:1.6:1.2 to obtain a negative electrode slurry, and the negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through processes such as rolling, slitting, and punching.

[0167] (3) Preparation of diaphragm:

[0168] Use commercial polypropylene diaphragms;

[0169] (4) Preparation of electrolyte:

[0170] A mixed solvent was prepared by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) at a mass ratio of 50:50, and then fully dried electrolyte salt LiPF6 was dissolved therein (1.0 mol / L) to obtain an electrolyte solution.

[0171] (5) Preparation of lithium-ion batteries

[0172] The positive electrode sheet, the separator and the negative electrode sheet are stacked in order to obtain the electrode core; the electrode core is placed in an outer package and baked; the electrolyte is injected into the dried lithium-ion battery, and a secondary battery is prepared through the processes of standing, forming, vacuum packaging, aging, and capacity division.

[0173] Comparative Example 2

[0174] A coating, which differs from Example 1 in that it does not include a lithium ion conductor material.

[0175] In this embodiment, an amphiphilic polymer coating mainly composed of propoxyglycerol triglycidyl ether (GPTE) is constructed on the surface of aluminum foil through coupling reaction and cross-linking reaction. The specific steps are as follows:

[0176] 1. Add the precursors of the amphiphilic material, propoxyglycerol triglycidyl ether (GPTE) and octadecylamine (ODA) (the mass ratio of the two is 50:1) into the mixed liquid of anhydrous ethanol and 1-methylpyrrole (V:V=100:0.01), and stir at room temperature for 6 hours and at 50°C for 15 minutes to obtain a uniform solution;

[0177] 2. Spray the above solution evenly on aluminum foil;

[0178] 3. Dry the aluminum foil at room temperature for 5 minutes, and heat at 150° C. for 1 hour to complete crosslinking and curing, thereby obtaining an aluminum foil with an amphiphilic polymer coating, the thickness of which is 2 μm;

[0179] 4. Preparation of a lithium-ion battery comprising the above-mentioned positive electrode sheet:

[0180] (1) Preparing a positive electrode sheet with the amphiphilic polymer coating on the surface of an aluminum foil:

[0181] The positive electrode active material LiFePO4, conductive carbon black (Super P) and binder polytetravinylidene fluoride (PVDF) are uniformly mixed in a proper amount of N-methylpyrrolidone (NMP) at a mass ratio of 97.3:1.2:1.5 to prepare a positive electrode slurry, and the positive electrode slurry is coated on the above-mentioned aluminum foil with the amphiphilic polymer coating, and the positive electrode sheet is prepared through rolling, slitting, punching and other processes;

[0182] (2) Preparation of negative electrode sheet:

[0183] The negative electrode active material artificial graphite, the conductive agent carbon black (Super P), the binder styrene butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC Na) are mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 95.5:1.7:1.6:1.2 to obtain a negative electrode slurry, the negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through rolling, slitting, punching and other processes;

[0184] (3) Preparation of diaphragm:

[0185] Use commercial polypropylene diaphragms;

[0186] (4) Preparation of electrolyte:

[0187] A mixed solvent was prepared by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) at a mass ratio of 50:50, and then fully dried electrolyte salt LiPF6 was dissolved therein (1.0 mol / L) to obtain an electrolyte solution.

[0188] (5) Preparation of lithium-ion batteries

[0189] The positive electrode sheet, the separator and the negative electrode sheet are stacked in order to obtain the electrode core; the electrode core is placed in an outer package and baked; the electrolyte is injected into the dried lithium-ion battery, and a secondary battery is prepared through the processes of standing, forming, vacuum packaging, aging, and capacity division.

[0190] Comparative Example 3

[0191] A coating, which differs from Example 1 in that it does not include an amphiphilic material.

[0192] In this embodiment, an oxide solid electrolyte Li1.4Al0.4Ti1.6(PO4)3 with a particle size of 50-100nm is selected as lithium ion conductive particles, and a coating containing only solid electrolyte nanoparticles is prepared on the surface of aluminum foil. The specific steps are as follows:

[0193] 1. Add Li1.4Al0.4Ti1.6(PO4)3 particles with a particle size of 50-100 nm into anhydrous ethanol solvent, stir rapidly at room temperature to fully disperse them, and use polyethylene glycol as a dispersant and ultrasonic methods to prepare a dispersion with a solid content of 0.1%;

[0194] 2. Spray the above dispersion evenly on the aluminum foil;

[0195] 3. Dry the aluminum foil at room temperature for 5 minutes, and heat at 150° C. for 1 hour to further evaporate the solvent, thereby obtaining an aluminum foil having a Li1.4Al0.4Ti1.6(PO4)3 nanoparticle coating, the coating thickness of which is 2 μm;

[0196] 4. Preparation of a lithium-ion battery comprising the above-mentioned positive electrode sheet:

[0197] (1) Preparing a positive electrode sheet with the lithium ion conductor coating on the surface of an aluminum foil:

[0198] The positive electrode active material LiFePO4, conductive carbon black (Super P) and binder polytetravinylidene fluoride (PVDF) are uniformly mixed in a proper amount of N-methylpyrrolidone (NMP) at a mass ratio of 97.3:1.2:1.5 to prepare a positive electrode slurry, and the positive electrode slurry is coated on the aluminum foil with the lithium ion conductor coating, and the positive electrode sheet is prepared through rolling, slitting, punching and other processes;

[0199] (2) Preparation of negative electrode sheet:

[0200] The negative electrode active material artificial graphite, the conductive agent carbon black (Super P), the binder styrene butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMCNa) are mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 95.5:1.7:1.6:1.2 to obtain a negative electrode slurry, and the negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through processes such as rolling, slitting, and punching.

[0201] (3) Preparation of diaphragm:

[0202] Use commercial polypropylene diaphragms;

[0203] (4) Preparation of electrolyte:

[0204] A mixed solvent was prepared by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) at a mass ratio of 50:50, and then fully dried electrolyte salt LiPF6 was dissolved therein (1.0 mol / L) to obtain an electrolyte solution.

[0205] (5) Preparation of lithium-ion batteries

[0206] The positive electrode sheet, the separator and the negative electrode sheet are stacked in order to obtain the electrode core; the electrode core is placed in an outer package and baked; the electrolyte is injected into the dried lithium-ion battery, and a secondary battery is prepared through the processes of standing, forming, vacuum packaging, aging, and capacity division.

[0207] Comparative Example 4

[0208] The difference from Example 1 is that unmodified aluminum foil is used.

[0209] Preparation of lithium-ion batteries:

[0210] (1) Preparation of positive electrode sheet:

[0211] The positive electrode active material LiFePO4, conductive carbon black (Super P) and binder polytetravinylidene fluoride (PVDF) are uniformly mixed in a proper amount of N-methylpyrrolidone (NMP) at a mass ratio of 97.3:1.2:1.5 to prepare a positive electrode slurry, and the positive electrode slurry is coated on an unmodified aluminum foil, and then subjected to processes such as rolling, slitting and punching to prepare a positive electrode sheet;

[0212] (2) Preparation of negative electrode sheet:

[0213] The negative electrode active material artificial graphite, the conductive agent carbon black (Super P), the binder styrene butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC Na) are mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 95.5:1.7:1.6:1.2 to obtain a negative electrode slurry, the negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through rolling, slitting, punching and other processes;

[0214] (3) Preparation of diaphragm:

[0215] Use commercial polypropylene diaphragms;

[0216] (4) Preparation of electrolyte:

[0217] A mixed solvent was prepared by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) at a mass ratio of 50:50, and then fully dried electrolyte salt LiPF6 was dissolved therein (1.0 mol / L) to obtain an electrolyte solution.

[0218] (5) Preparation of lithium-ion batteries

[0219] The positive electrode sheet, the separator and the negative electrode sheet are stacked in order to obtain the electrode core; the electrode core is placed in an outer package and baked; the electrolyte is injected into the dried lithium-ion battery, and a secondary battery is prepared through the processes of standing, forming, vacuum packaging, aging, and capacity division.

[0220] The following is an evaluation of the diaphragms, pole pieces and lithium-ion batteries prepared in the above Examples 1-5 and Comparative Examples 1-4 through wettability test, 1500-cycle lithium plating test and capacity retention test.

[0221] Performance Testing Methods

[0222] 1. Wettability test of diaphragm and electrode for aqueous solvent, oily solvent and electrolyte:

[0223] The present invention determines the wettability of the electrolyte by different types of solvents and the contact angles of the electrolyte on the surfaces of the diaphragm and the electrode material. A contact angle tester is used to test the static contact angle of the solvent and the electrolyte after they are dripped onto the sample surface for 6 seconds, and the results of 5 repeated tests are taken as the final result.

[0224] EC was selected as the representative of aqueous solvents, EMC as the representative of oily solvents, and the electrolyte was represented by the following formula: ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were prepared into a mixed solvent in a mass ratio of 50:50, and then fully dried electrolyte salt LiPF6 was dissolved therein (1.0 mol / L) to obtain an electrolyte.

[0225] 2. Battery cycle lithium deposition test:

[0226] The battery after 1500 cycles was disassembled to observe the lithium deposition on the interface. The degree of lithium deposition in the center of the pole piece was determined to evaluate the improvement effect of the lithium ion conductive super-amphiphilic coating provided by the present invention on the lithium deposition caused by the lack of liquid in the middle of the battery cell during the cycle.

[0227] Cycling conditions: 25°C, 1C / 1C, 1500 cycles.

[0228] Lithium deposition degree judgment standard: The percentage of lithium deposition area in the center of the pole piece to the total area of ​​the pole piece:

[0229]

[0230] 3. Capacity retention rate after 1500 cycles:

[0231] The cycle capacity retention rate of the battery cell after 1500 cycles is used as a basis to evaluate the effect of the lithium ion conductive super amphiphilic coating provided by the present invention on improving the cycle life.

[0232] Cycling conditions: 25°C, 1C / 1C, 1500 cycles.

[0233] Capacity retention rate calculation method: 1500-cycle discharge capacity / initial discharge capacity.

[0234] Test results:

[0235]

[0236]

[0237] The test results of Examples 1-5 show the technical effects of the super-amphiphilic coating that can conduct lithium ions on positive and negative electrodes and battery cells when applied to aluminum foil, copper foil and separator.

[0238] (1) The positive and negative electrodes and separators using the coating have super affinity for aqueous and oily solvents in the electrolyte, and their contact angles for aqueous EC and oily EMC solvents are both less than 5°, thereby achieving super affinity for the electrolyte (contact angle for the electrolyte is less than 5°).

[0239] (2) Furthermore, the positive and negative electrode sheets and separators with the coating have good wettability during the cycle process, which can accelerate the reabsorption of the electrolyte, improve the liquid absorption capacity of the battery cell, and help alleviate the extrusion of the electrolyte during the expansion process. After 1500 cycles, the battery cells using the positive and negative electrode sheets and separators with the coating have a low degree of lithium precipitation.

[0240] (3) Correspondingly, its capacity retention rate for 1500 cycles is relatively excellent.

[0241] Comparison of Comparative Examples 1, 2, 3 and 4 with Example 1 illustrates the necessity of combining the amphiphilic material and the lithium ion conductor nanomaterial when constructing the super amphiphilic coating capable of conducting lithium ions.

[0242] (1) Comparative Example 4 is a positive electrode sheet and a battery cell prepared by unmodified aluminum foil. The contact angle of the positive electrode sheet to EC, EMC and electrolyte is large, and the degree of lithium deposition corresponding to its 1500 cycles is large, and the cycle capacity retention rate is low;

[0243] (2) The coating structure of Comparative Example 1 uses 5 μm-diameter Li1.4Al0.4Ti1.6(PO4)3 particles coated with propoxyglycerol triglycidyl ether polymer, and the coating formed lacks the micro-nanostructure required for super-amphiphilic function, so the affinity for oily and aqueous solvents and electrolytes is only improved to a certain extent;

[0244] (3) In Comparative Example 2, only propoxyglycerol triglycidyl ether polymer is used as a coating, and the constructed interface only has an amphiphilic function, which is much lower than the wettability of the positive electrode sheet with the coating in Example 1 to EC, EMC and electrolyte;

[0245] (4) Comparative Example 3 uses nano-Li1.4Al0.4Ti1.6(PO4)3 electrolyte particles with a particle size of 50-100nm to construct a coating. Due to its polarity, it has a certain affinity for both EC solvents and electrolytes. However, compared with the super amphiphilic coating constructed in Example 1, its affinity is still relatively low, the degree of lithium plating during the cycle is relatively high, and the capacity retention rate is correspondingly poor.

[0246] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A super-amphiphilic coating capable of conducting lithium ions, characterized in that: It comprises an amphiphilic material and a lithium ion conductor nanomaterial; the amphiphilic material is coated on the surface of the lithium ion conductor nanomaterial; The amphiphilic material comprises at least one of propoxyglycerol triglycidyl ether polymer, polyvinyl pyrrolidone, polydopamine, polyethylene glycol-polytetramethyl ether glycol copolymer or polyethylene glycol-polydimethylsiloxane copolymer; The lithium ion conductor nanomaterial includes at least one of a NASICON type oxide solid electrolyte, a LISICON type oxide solid electrolyte, a Garnet type oxide solid electrolyte, a Perovskite type oxide solid electrolyte or an Antiperovskit type oxide solid electrolyte; The particle size of the lithium ion conductor nanomaterial is 10200 nm.

2. The super-amphiphilic coating capable of conducting lithium ions according to claim 1, characterized in that: The mass ratio of the amphiphilic material to the lithium ion conductor nanomaterial is 0.01:110:

1.

3. The super-amphiphilic coating capable of conducting lithium ions according to claim 1, characterized in that: The static contact angle of the water-based solvent of the super-amphiphilic coating is less than 5°; the static contact angle of the oil-based solvent is less than 5°.

4. The super-amphiphilic coating capable of conducting lithium ions according to claim 1, characterized in that: The NASICON-type oxide solid electrolyte includes Li 1.4 Al 0.4 Ti 1.6 (PO4)3 or Li 1.5 Al 0.5 Ge 1.5 (PO4)3; The LISICON-type oxide electrolyte includes γLi3PO4; The Garnet-type oxide solid electrolyte includes Li7La3Zr2O 12 or Li5La3Ta2O 12 ; The Perovskite-type oxide solid electrolyte includes Li 0.5 La 0.5 TiO3; The Antiperovskite-type oxide solid electrolyte includes Li3OCl.

5. The method for preparing the super-amphiphilic coating capable of conducting lithium ions according to any one of claims 1 to 4, characterized in that: The following steps are involved: The amphiphilic material or its precursor, a lithium ion conductor nanomaterial and a solvent are mixed to form a dispersion, and then the dispersion is applied and dried to prepare the super amphiphilic coating capable of conducting lithium ions; The solvent includes at least one of ethanol, deionized water, n-hexane, tetrahydrofuran (THF), heptane, isopropanol, carbon trichloride or carbon tetrachloride.

6. The preparation method according to claim 5, characterized in that: In the dispersion, the mass proportion of the lithium ion conductor nanomaterial is 0.1%-10%.

7. Use of the super-amphiphilic coating capable of conducting lithium ions according to any one of claims 1 to 4 in a battery.

8. A diaphragm, characterized in that: It comprises a base film, the surface of which is coated with the super-amphiphilic coating capable of conducting lithium ions as claimed in any one of claims 1 to 4.

9. A pole piece, characterized in that: It comprises a current collector, the surface of which is coated with the super-amphiphilic coating capable of conducting lithium ions as claimed in any one of claims 1 to 4.

10. A lithium ion battery, characterized in that: It comprises the diaphragm according to claim 8 and / or the pole piece according to claim 9.

Citation Information

Patent Citations

  • Lithium ion battery separator containing poly-dopamine and ceramic coatings

    CN103682216A

  • Diaphragm, method for preparing diaphragm and secondary battery comprising diaphragm

    CN105789538A

  • Composite diaphragm and preparation method and use thereof

    CN110391386A

  • Super-hydrophobic material capable of conducting lithium ions as well as preparation method and application thereof

    CN112701345A

  • Functional diaphragm for lithium-sulfur battery, and preparation method and application thereof

    CN113067096A

Cited By

  • Modified polytetrafluoroethylene microporous membrane as well as preparation method and application thereof

    CN122315250A